Decoding the Syrian Crisis through Arabic Political Caricature: A Jakobsonian Semiotic Study - Husnul Khotimah; M. Anwar Masadi (LISANIA: Journal of Arabic Education and Literature, 2025)
Caricatures are not merely visual humor but function as powerful instruments of socio-political critique. This study analyzes three caricatures by Osama Hajjaj that depict the condition of Syria following the collapse of Bashar al-Assad’s regime. Guided by Roman Jakobson’s semiotic framework, the analysis applies six language functions: addresser, addressee, message, context, code, and contact to explore the layered meanings embedded in Hajjaj’s works. Jakobson’s model is relevant for visual texts because its communicative functions operate through both verbal and non-verbal signs, allowing caricatures to be interpreted as structured messages. A qualitative approach was employed, with primary data obtained from caricatures published on Hajjaj’s Instagram account and secondary data drawn from scholarly literature and credible news reports. The results demonstrate that Hajjaj’s caricatures transcend mere satire of Assad’s leadership; they articulate broader grievances regarding foreign intervention, systemic repression, and the uncertainties surrounding political transition. Furthermore, the visual narratives reveal how caricatures can simultaneously criticize power structures and express collective resistance. This research contributes to the field of semiotics by expanding Jakobson’s framework into the analysis of political caricatures and provides new insights into visual communication in Middle Eastern contexts. The novelty of this study lies in its focus on Syrian-themed caricatures, a topic rarely examined in previous research, and in its analysis of the interaction among Jakobson’s functions to reveal the ideological dimensions within Hajjaj’s works.